Quaternary Geology and Environment of China - Liu, Tung-sheng (Beijing, Berlin : China Ocean Press, Springer, 1985)
Quaternary Stratigraphy. Lithology and Genesis of Quaternary Deposits. Quaternary Fauna and Flora. Quaternary Paleogeography. Prehistoric Man and His Material Culture. Natural Resources of Quaternary Deposits and Their Utilisation. Protection of the Natural Environment
Quaternary Research Ass. = Quaternary Research Association of China
bibliogr. dissém.